Factors in companies' decisions on outsourcing :|an empirical study in Turkey - Aliyeva, Sevinj. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Outsourcing has been widely used by organizations as a means to reduce costs, increase flexibility, and achieve efficiency. However, in the past few decades outsourcing has moved beyond a simple purchasing process and become a strategic tool for companies. In this transition process, soft factors such as trust and cultural compatibility have become superior to the factors that have traditionally affected the outsourcing decisions most such as price. This study aims to explore the factors that affect the outsourcing decision of companies in Turkey and examines whether there are specifically important factors for different outsourced functions. The purpose of this study is to determine which stage of the abovementioned transition process the Turkish firms are in and what they seek for in their suppliers. Data have been collected from 45 companies that operate in Turkey via online-administered questionnaires and analyzed by reliability, linear regression, and ANOVA analysis. The results show that regardless of the function that is being outsourced the most important three factors for Turkish firms are price, quality, and strong references. Trust, cultural compatibility, and open communication were found to be the least crucial factors when making the outsourcing decision. Findings imply that companies in Turkey still use outsourcing mainly for cost-cutting purposes. Our study sketches the general outsourcing environment in Turkey and presents applicable findings for both outsourcing companies and suppliers.
Keywords: Contracting out -- Turkey.; Offshore outsourcing -- Turkey.